O uso do geoprocessamento na espacialização e avaliação das Áreas de Preservação Permanente: Cidade de Porto Velho-RO - Helen Rose Oliveira da Silva; Siane Cristhina Pedroso Guimarães; Liliana Borges de Oliveira (Confins)
The aim of this study is to delimit the Permanent Preservation Area (PPA) in the urban area of Porto Velho city, with bands of 15m to 30m. As a checking base geoprocessing was associated with the use of remote sensing. These techniques enable and increase the efficiency in controlling the degradation of such areas and can be easily used by the government monitoring department. SPOT images with spatial resolution of 2.5 m were used as well as the WorldView 50 cm spatial resolution. The maps were elaborated using the free version of SPRING 5.2 software from the National Institute for Space Research, INPE. It was also used as a data, a population map for districts of the City Department of Planning – SEMPLA. While the data was being handled it was possible to calculate a total of 1267,03 ha of 30m PPA from which 65,4% ha had already been cut down. The 15 m PPA were summed to 956, 46 ha, with a 66,4% deforestation rate. At the end of this study it was observed that, even with the decrease in the vegetation strip of 15 m, as it is suggested by the law of usage and occupation of urban areas in Porto Velho, there is still a deficit of preserved PPA for the city. This is a sign that deforestation is still constant, reflecting an anthropization increasingly high in urban areas. The final result also showed that the neighborhoods that have had most deforestation in PPA were Nova Floresta, Floresta and Mato Grosso.